Effectiveness of Family-oriented Education on Self-care behaviors of Patients with Acute Myocardial Infarction: A Randomized Clinical Trial - Zahra Molazem; Elham Taheri; Majid Najafi Kalyani (Shiraz University of Medical Sciences, 2024)
Background: Proper self-care practices play a crucial role in the well being and longevity of patientswith cardiovascular disease. To effectively engage in self-care, it is imperative for patients to receiveadequate education and training on the self-care process. This study was conducted to determine theeffect of family-oriented education (FOE) on the self-care behaviors of patients with acute myocardialinfarction (AMI).Methods: In this randomized clinical trial study, 70 patients hospitalized in two hospitals in Shirazduring November 2021-April 2022 participated after the first AMI. Patients were randomly assignedinto control (N=35) and intervention groups (N=35) based on random allocation. In the interventiongroup, an educational program was conducted for patients and active family members during threesessions of 45 to 60 minutes. The control group received routine care. Demographic information formand Self-Care Agency scale was completed by the patients before the educational intervention, onemonth, and two months after the educational intervention. Data analysis was done through SPSS 22using Chi-square test, independent t-test, Fisher's exact, and Friedman test. P˂0.05 was considered asthe statistical significance level.Results: There was no significant difference in self-care behaviors between the two groups before theintervention (P=0.71). The mean score of self-care behaviors in patients one month (P<0.001) and twomonths (P<0.001) after FOE in the intervention group showed a statistically significant difference withthe control group. Also, the mean score of self-care behaviors two months after the education in theintervention group was significantly higher than before and one month after the intervention (P<0.001).Conclusion: Given the positive effect of FOE on self-care behaviors of patients with AMI, it isrecommended that educational interventions related to the treatment plan of these patients with theparticipation of families should be conducted.Trial Registration Number: IRCT20211116053078N1